2022
DOI: 10.3390/tropicalmed7110351
|View full text |Cite
|
Sign up to set email alerts
|

Potential Nosocomial Infections by the Zika and Chikungunya Viruses in Public Health Facilities in the Metropolitan Area of Recife, Brazil

Abstract: Since 2015, the Dengue, Zika, and Chikungunya viruses gained notoriety for their impact in public health in many parts of the globe, including Brazil. In Recife, the capital of Pernambuco State, the introduction of ZIKV impacted human population tremendously, owing to the increase in the number of neurological cases, such as the Guillain–Barré and congenital Zika disorders. Later, Recife was considered to be the epicenter for ZIKV epidemics in Brazil. For arboviral diseases, there are some risk factors, such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
0
0
Order By: Relevance
“…Krokovsky et al [40,41] identified multiple pools of Cx. quinquefasciatus that tested positive for ZIKV in Recife (PE) between 2016 and 2017, and detected ZIKV in pools of Cx.…”
Section: Zika Virus (Zikv): Orthoflavivirus Zikaensementioning
confidence: 99%
“…Krokovsky et al [40,41] identified multiple pools of Cx. quinquefasciatus that tested positive for ZIKV in Recife (PE) between 2016 and 2017, and detected ZIKV in pools of Cx.…”
Section: Zika Virus (Zikv): Orthoflavivirus Zikaensementioning
confidence: 99%